The Impact of Donor and Recipient Renal Dysfunction on Cardiac Allograft Survival: Insights into Reno-Cardiac Interactions - Laur, Olga (J Card Fail, 2015)
BACKGROUND: Renal dysfunction (RD) is a potent risk factor for death in patients with cardiovascular disease. This relationship may be causal since experimentally induced RD produces findings such as myocardial necrosis and apoptosis in animals. Cardiac transplantation provides an opportunity to investigate this hypothesis in humans. METHODS AND RESULTS: Cardiac transplantations from the UNOS registry were studied (n=23,056). RD was defined as an estimated glomerular filtration rate < 60 ml/min/1.73m(2). RD was present in 17.9% of donors and 39.4% of recipients. Unlike multiple donor characteristics, such as older age, hypertension or diabetes, donor RD was not associated with recipient death or retransplantation (age-adjusted HR=1.00, 95% CI 0.94–1.07, p=0.92). Moreover, in recipients with RD the highest risk for death or retransplantation occurred immediately post-transplant (0–30 day HR=1.8, 95% CI 1.54–2.02, p<0.001) with subsequent attenuation of the risk over time (30–365 day HR=0.92, 95% CI 0.77–1.09, p=0.33). CONCLUSIONS: The risk for adverse recipient outcomes associated with RD does not appear to be transferrable from donor to recipient via the cardiac allograft and the risk associated with recipient RD is greatest immediately following transplant. These observations suggest that the risk for adverse outcomes associated with RD is likely primarily driven by non-myocardial factors.